2008
DOI: 10.1190/1.2981184
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir monitoring and characterization using satellite geodetic data: Interferometric synthetic aperture radar observations from the Krechba field, Algeria

Abstract: Deformation in the material overlying an active reservoir is used to monitor pressure change at depth. A sequence of pressure field estimates, eleven in all, allow us to construct a measure of diffusive travel time throughout the reservoir. The dense distribution of travel time values means that we can construct an exactly linear inverse problem for reservoir flow properties. Application to Interferometric Synthetic Aperture Radar (In-SAR) data gathered over a CO 2 injection in Algeria reveals pressure propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 59 publications
1
95
0
Order By: Relevance
“…9. The spatial pattern of surface uplift is consistent with the uplift spread computed by Preisig and Prévost 7 and the satellite imagery presented in Onuma and Ohkawa 5 and Bohloli et al 6 …”
Section: Benchmark To the Case Of The In Salah Projectsupporting
confidence: 72%
See 2 more Smart Citations
“…9. The spatial pattern of surface uplift is consistent with the uplift spread computed by Preisig and Prévost 7 and the satellite imagery presented in Onuma and Ohkawa 5 and Bohloli et al 6 …”
Section: Benchmark To the Case Of The In Salah Projectsupporting
confidence: 72%
“…Ground deformation of up to 7 mm/year has been measured around each of the three injection wells at the In Salah project, Algeria, the largest on-shore CO 2 storage project in the world. 5,6 These geomechanical issues have become a public concern and a research and industry interest for future reservoir integrity design and risk assessment of CO 2 storage projects.…”
Section: J Nmentioning
confidence: 99%
See 1 more Smart Citation
“…At the KB502, on the other hand, the injection scheme has been more complex with more variations of the injection rates and the uplift pattern is also more complex with two parallel uplift lobes rather than one single uplift lobe. The two uplift lobes was interpreted in Vasco et al (2008b) to be caused by pressure diffusion along two parallel permeable zones within reservoir. That would suggest that permeability at KB502 is strongly heterogeneous affected by the degree of fracturing and perhaps by intersecting faults (Ringrose et al, 2009).…”
Section: Krechba Site and Observed Ground Deformationsmentioning
confidence: 99%
“…A ground uplift of around 5 mm/yr was measured on top of the three horizontal injection wells using satellite geodetic data (Vasco et al, 2008;Mathieson et al, 2009;Onuma and Okhawa, 2009). Simulation results showed that such ground uplift rate could be reproduced by considering pressure increase and volumetric expansion of both the injection zone and the overlying caprock (Rutqvist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%